Ethnicity and Wage Determination in Ghana - Barr, Abigail; Oduro, Abena (World Bank, Washington, DC, 2014)
The authors look at earnings differentials between members of different ethnic groups, and between employers' relatives, unrelated members of the same ethnic group, and other workers in Ghana's manufacturing sector. They find that a significant proportion of the earnings differentials identified between ethnic groups can be explained with reference to a fairly standard set of observations about workers' characteristics. Labor market segregation along ethnic lines - combined with considerable variation in employers' characteristics (especially educational attainment and family background, possibly because of discrimination in other markets) - accounts for most of the remaining differentials. Northerners earn considerably less than other groups, mainly because they are less educated. The Other Akan earn much more than the relatively low-earning Asante, Fante, and Ewe. There is no evidence of discrimination between ethnic groups, although there is evidence of discrimination in favor of inexperienced workers from the same ethnic group, who can be assessed, and matched with jobs more easily than similar workers from other ethnic groups. Finally, workers who are related to their employers, earn a considerable premium, possibly because they contribute more to productivity than their fellow workers (perhaps through an effect on "esprit de corps"). The authors' results draw attention to some startling differences in educational, and labor market attainment between groups. A strong case can be made for including such issues in the policy debate.